Hydrogen technology adoption analysis in Africa using a Doughnut-PESTLE hydrogen model (DPHM) - Mukelabai, Mulako Dean; Wijayantha, Upul K. G.; Blanchard, Richard E. (Elsevier, 2022)
The hydrogen economy requires the right conditions to produce hydrogen by sustainable routes and provide it to local and international markets for suitable applications. This study evaluated the political, economic, social, technological, legal, and environmental (PESTLE) conditions that can be instrumental in adopting hydrogen technologies most effectively by encapsulating aspects relevant to key stakeholders from hydrogen technology developers through to end-users. For instance, the analysis has shown that countries within a government effectiveness index of 0.5 and −0.5 are leading the planning of hydrogen economies through strategic cooperation with hydrogen technology developers. Furthermore, the combination of a Doughnut and PESTLE analysis created a novel approach to assessing the adoption of hydrogen technologies while evaluating the impact of the hydrogen economy. For instance, the estimated ammonia demand in 2050 and subsequent anthropogenic nitrogen extraction rate will be about two and a half times more than the 2009 extraction rate.
Keywords: DPHM; Hydrogen production; Political and economic; Social and technology; Legal and environment; Planetary boundaries